(untitled) (The Journal of Modern Project Management, 2022)
Large-scale engineering and construction projects are subject to a great level of uncertainty which lead planners to use time buffers and add contingencies to the estimated budget. However, the size of the buffers and the contingency amounts are usually arbitrarily established and projects still encounter severe time and cost overruns. In this paper, a robust planning approach for tactical planning of large-scale engineering and construction projects is proposed. The approach relies on a simple resource buffering strategy applied to the aggregate periods. An extensive simulation-based experiment was conducted to test the robustness and performance of the proposed approach. Results show that the proposed buffering strategy can considerably reduce project cost variations and can provide comparable performance results with those obtained using a disaggregated approach, especially on instances characterized by a large number of resource groups.